2014
DOI: 10.1186/1880-6805-33-19
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres are elongated in rats exposed to moderate altitude

Abstract: BackgroundLeukocyte telomere length has been shown to be associated with life span. Hypoxia-associated changes of telomere length have been detected in cell cultures, but no in vivo studies have reported the changes of telomere length under different hypoxic conditions. This study aimed to evaluate the effects of altitude on telomere length in rat leukocytes.MethodsOne hundred and ten male Wistar rats were randomized into 3 groups and maintained at sea-level (altitude of 10 m) (SL group, n = 10), moderate alti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…15 Wang's experimental study (2014) showed that a group of male rats with low SOD activity had shorter telomeres. 17 There was a significant positive correlation between SOD activity and telomere length of Minangkabau ethnic men, so some efforts to increase SOD activity can be done as an effort to prevent telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Wang's experimental study (2014) showed that a group of male rats with low SOD activity had shorter telomeres. 17 There was a significant positive correlation between SOD activity and telomere length of Minangkabau ethnic men, so some efforts to increase SOD activity can be done as an effort to prevent telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Research by Wang showed that groups which experienced increased oxidative stress and low SOD activity had shorter telomeres. 17 The study aimed to examine the correlation between SAFA and SOD with the telomere length of Minangkabau ethnic men.…”
mentioning
confidence: 99%
“…Plasma SOD enzyme activity and telomere length SOD is an endogenous antioxidant that functions in the body's defense system against ROS. This enzyme plays a role in catalyzing the conversion reaction of superoxide radical (O2-) to hydrogen peroxide and molecular oxygen and is the only enzyme that has the ability to eliminate the toxic effects of superoxide radicals [24].…”
Section: Telomere Lengthmentioning
confidence: 99%
“…Hypoxia is one of the most important environmental factors for HAPE, which could influence the quantity of liquid escaping from the pulmonary vasculature . A previous study reported that telomere length was significantly longer at moderate attitude than at sea‐level or at simulated high attitude, and that the expression of TERT and HIF‐1α changed in a manner similar to leukocyte telomere length under hypoxic conditions in a study in Wistar rats . Telomere length is determined by the balance of processes that shorten and lengthen the telomere .…”
Section: Introductionmentioning
confidence: 97%